Role of institutions of exchange rate and economic growth in South Africa - Seraj, Mehdi; Coskuner, Cagay; Alhassan, Abdulkareem (Emerald Group Publishing Ltd, 2025)
PurposeThe use of exchange rate policies to stimulate economic growth (EG) has been the major macroeconomic policy of many economies. Hence, the attention of researchers and policymakers was drawn to the effect of undervaluation and/or overvaluation of currencies on sustainable EG. However, less attention has been paid to the importance of quality of economic institutions in shaping the relationship between exchange rate and EG. This study aims to explore the role of institutions of exchange rate and EG in South AfricaDesign/methodology/approachThis study, therefore, examines the role of economic institutions in the real exchange rate economic growth nexus by using auto regressive distributed lags model and vector error correction model for causality during the period 1971 to 2018. Also, Bayer and Hank method has applied for cointegration between the variables.FindingsThe findings show that both real exchange rate and economic institutions have a negative effect on EG in both short-run and long-run. This implies that undervaluation has a negative effect on EG in South Africa. Therefore, the study concludes that undervaluation has a negative effect on EG in South Africa particularly when the quality of economic institutions is accounted for. The finding supports the J-curve hypothesis but is contrary to the Rodrik hypothesis. Hence, devaluation is not a desirable exchange rate policy for the South African economy.Originality/valueThe study, therefore, recommends that developing countries like South Africa should focus on other viable exchange rate policies such as rather than undervaluation of currency to enhance EG.
Keywords: Economic institutions; Real exchange rate; Economic growth; Bayer and Hanck combined cointegration test; VECM Granger causality approach; F31; F43